The application of electro-coagulation in biodiesel wastewater treatment - Syed Mohd, Syed Ahmad Fauzan; Daud, Zawawi; Mohd Asharuddin, Syazwani; Hassan, Azrul (Penerbit UTHM, 2020)
A large quantity of oily wastewater is generated by biodiesel refineries which results in terrible environmental pollution and resource utilization problems. This wastewater must be treated before being released into the environment due to it normally rich in biological oxygen demand (BOD) and chemical oxygen demand (COD) which usually have damaging and harmful effects on plants, sea, river as well as surface and groundwater sources. Conventional biodiesel wastewater treatment methods such as gravity separation and skimming, air flotation, coagulation, de-emulsification and flocculation, posses several disadvantages including high operation cost, low efficiency, corrosion and recontamination problems. Indeed, most of these conventional methods unable to remove the micron or submicron sized oil droplets efficiently. Currently, new processes for efficient and adequate treatment of various industrial wastewaters with relatively low operating costs have been developed to meet the strict environmental regulations. At this point, the electrocoagulation process has attracted a great deal of attention in treating industrial wastewaters because of its versatility and environmental compatibility. Therefore, in this chapter, the advatages and application of electro-coagulation techniques were reviewed and discussed.